An inventory of cryospheric landforms in the arid diagonal of South America (high Central Andes, Atacama region, Chile) - García, Ayôn (2017)
An integral, glacial and periglacial, inventory of the cryosphere in the Atacama region in Chile was carried out to estimate the amount of frozen water reserves in this arid to hyper-arid region. The inventory was carried out with medium to high spatial resolution satellite images and resulted in a total of 168,908 ha of landforms with significant ice content in one of the most fragile Andean ecosystems: the semi-arid – hyper-arid zones. This study shows an integral mapping of the cryosphere including glaciers and ice-bearing periglacial landforms. The different ice landforms in the Atacama region shows a progressive change in the landforms containing ice responding to the northwards increase of aridity upon entry to the South American hyper-arid axis. The main change observed is that uncovered glaciers are not present north of 26.5°S, being replaced by creeping permafrost landforms. Uncovered glaciers may produce more water annually compared to other ice-bearing landforms, but they only represent 2.7% of the cryospheric area. However, cryoforms containing a mixture of ice, sediment and rock fragments could be more important as water reserves because of their large extensions that cover c. 97% of the total area of ice-bearing landforms mapped. It also shows that the water-supply potential of ice-bearing periglacial landforms could be much higher than that of the glaciers in arid zones. The comparison with the previous inventory of 1987 suggests a reduction of 34% of uncovered glaciers, which is consistent with the aridization process observed in almost all of northern Chile. These findings reinforce the fact that glaciers and other types of permanent ice-bearing landforms need to be inventoried together if the objective is to provide the society with a realistic view of the distribution of the cryospheric hydrological resources in desert regions.